2023
DOI: 10.1038/s41598-023-45344-4
|View full text |Cite
|
Sign up to set email alerts
|

Omega 3 fatty acid improves sexual and erectile function in BPF-treated rats by upregulating NO/cGMP signaling and steroidogenic enzymes activities

Adeyemi Fatai Odetayo,
Luqman Aribidesi Olayaki

Abstract: Bisphenol F (BPF) is an environmental pollutant that has been implicated in sexual dysfunction. Omega 3 fatty acid (O3FA), on the other hand, is an antioxidant with the ability to improve fertility indices. However, no study has explored the possible ameliorative effect of O3FA on BPF-induced sexual dysfunction. Thus, the effect of BPF and/or O3FA on male sexual performance was investigated. Male Wistar rats were randomized into 6 groups, corn oil-treated, O3FA low and high dose (100 and 300 mg/kg), BPF-treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…LH stimulates the testis to produce testosterone (steroidogenesis), while FSH stimulates Sertoli cells to produce sperm (spermatogenesis). Also, the testosterone produced from the testis assists in spermatogenesis [ 31 ]. The synthesized testosterone inhibits the pituitary gland's and hypothalamus's activities to maintain its optimal circulatory level [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…LH stimulates the testis to produce testosterone (steroidogenesis), while FSH stimulates Sertoli cells to produce sperm (spermatogenesis). Also, the testosterone produced from the testis assists in spermatogenesis [ 31 ]. The synthesized testosterone inhibits the pituitary gland's and hypothalamus's activities to maintain its optimal circulatory level [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…GnIH also acts by downregulating mRNA levels of luteinizing hormone beta-subunit (LHβ) and inhibiting its release from the anterior pituitary gland ( 16 , 80 ). GnIH can also inhibit LH synthesis via its stimulatory effect on prolactin secretion ( 81 ), which is a potent inhibitor of LH secretion ( 82 ). Its action on follicle-stimulating hormone beta-subunit (FSHβ) is not clear since its studies in quail have shown no effect on mRNA levels or FSH release.…”
Section: Gnihmentioning
confidence: 99%